Qualitative social network analysis: studying the field through the bibliographic approach - Kim, Aryuna; Maltseva, Daria (Quality & quantity, 2024)
This paper presents the results of a study on the development of qualitative social network analysis (QSNA) and its evolution over time, using the analysis of bibliographic networks. The dataset consists of articles from the Web of Science Clarivate Analytics database obtained by searching for the keyword“Social network* + (Qualitative OR Mixed method*)”(in total 21,823 publications). From the data, we constructed a citation network, which was followed by an evaluation of QSNA field’s growth and the identification of the most cited works. Using the normalized Search path count weights, we extracted the Main path and Key-routes in the citation network. Starting from 1988, when the first works appeared, the field has grown significantly. The analysis of the citation network shows that there are two main scientific spheres where QSNA was developed—in the social science and the medical science. In the social science the main empirical research subjects are migrant networks and teacher’s networks. In the medical science the research object moved from sexual contacts to social contacts in infection studies.